Duas formas de pensar: insights da economia comportamental e inteligência artificial nos processos decisórios de controle externo do Tribunal de Contas da União (TCU) - Caldera, Loana Costa Irmão (2023)
The case study carried out with the TCU judgments sought to develop a method to identify heuristics and behavioral biases in external control judgments. Conditions of the institutional environment linked to collegiate judgment processes and the use of mental systems defined by Behavioral Economics (BE) associated with the use of heuristics and biases were investigated (TVERSKY; KAHNEMAN, 1974). For this, content analysis and discourse analysis techniques were used to map expressions that could lead to the identification of cognitive biases in TCU judgments, through the exploration of decision-making manifestations, seeking to obtain a detailed understanding of the contexts of collegiate judgments. The results found showed that the majority of judgments were based on expressions of certainty, while just over 20% met the criteria established as uncertainty. In addition, the existence of implicit associations linked to Brazilian education was identified, revealing, together with the collegiate group, the formation of stereotypes about teaching institutions, students and teachers.